2017
DOI: 10.1111/idh.12304
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Education and Promotion Programmes: Meta‐Analysis of 17‐Year Intervention

Abstract: This study found that past OHEPIs are effective and positive impacts on dental visits, attitudes, as well as brushing and flossing behaviours during 3 months post-intervention among children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 23 publications
(43 reference statements)
4
60
0
14
Order By: Relevance
“…Also, one applicable index for assessing the condition of dental and oral health is the number of decayed, missed and filled teeth (DMFT) and this index comprises the number of decayed, missing, and filled teeth in a person [35]. Moreover, studies investigating oral health status have reported DMFT as a scientifically accepted index to elucidate the condition of dental and oral health [16,18,22,[36][37][38][39]. Thus, the aim of our study was to perform a systematic review of the literature and meta-analysis in order to investigate relationship between drug use and oral health condition.…”
Section: Introductionmentioning
confidence: 99%
“…Also, one applicable index for assessing the condition of dental and oral health is the number of decayed, missed and filled teeth (DMFT) and this index comprises the number of decayed, missing, and filled teeth in a person [35]. Moreover, studies investigating oral health status have reported DMFT as a scientifically accepted index to elucidate the condition of dental and oral health [16,18,22,[36][37][38][39]. Thus, the aim of our study was to perform a systematic review of the literature and meta-analysis in order to investigate relationship between drug use and oral health condition.…”
Section: Introductionmentioning
confidence: 99%
“…Providing health education to exposed or susceptible individuals, the human factor of prevention, control, treatment, and dealing with health issues is pivotal to the control and prevention of the disease . Since the theory‐based interventions supply a feasible framework to improve interventions and a guide for evaluating them and they have more useful effects on health‐related behaviors, they are more beneficial than the nontheoretical methods . Results of the studies have shown that theory‐based interventions may motivate people to change their attitudes and behaviors in exposure to the sunlight .…”
Section: Introductionmentioning
confidence: 99%
“…9 Since the theory-based interventions supply a feasible framework to improve interventions and a guide for evaluating them and they have more useful effects on health-related behaviors, they are more beneficial than the nontheoretical methods. [10][11][12][13] Results of the studies have shown that theory-based interventions may motivate people to change their attitudes and behaviors in exposure to the sunlight. 14 Rajers has introduced this theory for the first time in 1975, and after that, the theory was recognized as a framework to predict health-related behaviors and modeling health educational interventions.…”
mentioning
confidence: 99%
“…This study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines as described previously 2,8,20 and was registered in PROSPERO (CRD42018084308). The corresponding author did the systematic review for this article.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…1 Furthermore, oral health is an essential component of general health and quality of life. 2,3 Oral health is considered as a multifaceted phenomenon, including the ability to speak, smile, smell, taste, touch, chew and swallow, as well as the ability to express a range of emotions through facial expressions with confidence and without pain, discomfort and disease of the craniofacial complex. Moreover, oral health is influenced by the values and attitudes of individuals and communities and reflects the physiological, social and psychological attributes that are essential to the quality of life.…”
mentioning
confidence: 99%